2016
DOI: 10.1016/j.solidstatesciences.2015.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of crystal structure of SrLa(FeTi)O 6 and BaLa(FeTi)O 6 perovskites by rietveld refinement

Abstract: The structures of the recently reported ordered perovskites SrLa(FeTi)O 6 and BaLa(FeTi)O 6 have been revisited using Rietveld analysis of the powder x-ray diffraction data.Our studies clearly show that earlier authors have incorrectly reported the tetragonal structure in the I4/m space group for SrLa(FeTi)O 6 and the cubic structure in the Fm3 m space group for BaLa(FeTi)O 6 . The correct structure is found to be orthorhombic in the Pnma space group for SrLa(FeTi)O 6 while cubic in the Pm3 m space group for B… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…Thus we concluded the monoclinic (P2 1 /n) symmetry of these double perovskites. 44,46 The crystal structure derived from the Raman spectra of Ba 2 Ln 2/3 TeO 6 (Ln = La, Pr, Nd, Sm, and Eu) is thus confirmed by Rietveld refinement of the XRD patterns. All the patterns were fitted using the monoclinically distorted unit cell with P2 1 /n symmetry.…”
Section: ■ Experimental Sectionmentioning
confidence: 68%
“…Thus we concluded the monoclinic (P2 1 /n) symmetry of these double perovskites. 44,46 The crystal structure derived from the Raman spectra of Ba 2 Ln 2/3 TeO 6 (Ln = La, Pr, Nd, Sm, and Eu) is thus confirmed by Rietveld refinement of the XRD patterns. All the patterns were fitted using the monoclinically distorted unit cell with P2 1 /n symmetry.…”
Section: ■ Experimental Sectionmentioning
confidence: 68%
“…Furthermore, the crystal parameters obtained for the LaBaFeTiO 6 phase are consistent with those reported in the literature. 18 …”
Section: Resultsmentioning
confidence: 99%
“…Based on the literature survey, there are only two papers concerning the double perovskite LaBaFeTiO 6 , which cover the structural analysis and magnetic study by Mössbauer spectroscopy. 18,19 These studies revealed that this material crystallizes in a Pm 3̄ m cubic symmetry with a disordered distribution of Fe/Ti ions on the B-sites. 18 In addition, Mössbauer spectroscopic measurements (at 80 K and 300 K) pointed to the paramagnetic feature of this double perovskite with a trivalent high spin state for the iron ions.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations